2021
DOI: 10.1017/wet.2021.66
|View full text |Cite
|
Sign up to set email alerts
|

Influence of time of day on dicamba and glyphosate efficacy

Abstract: Renewed interest in studying auxin herbicides (WSSA group 4) is increasing due to the release of genetically engineered crop varieties that are tolerant to PRE and POST applications of specific formulations of dicamba. The development of auxin-resistant crops was in response to the development of herbicide-resistant weed species to glyphosate and other herbicides. Research was conducted at multiple field locations in Georgia in 2018 and 2019 to examine weed control when POST herbicides were applied to dicamba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Because there was no variation of control or height reduction, ANOVA could not be conducted. This result was expected, as ivyleaf morningglory is highly susceptible to both dicamba and glufosinate applied individually (Everman et al 2007;Kalina et al 2021;Merchant et al 2013). Control and height reduction data were not subjected to Colby's equation because of the complete control achieved.…”
Section: Ivyleaf Morningglorymentioning
confidence: 74%
See 2 more Smart Citations
“…Because there was no variation of control or height reduction, ANOVA could not be conducted. This result was expected, as ivyleaf morningglory is highly susceptible to both dicamba and glufosinate applied individually (Everman et al 2007;Kalina et al 2021;Merchant et al 2013). Control and height reduction data were not subjected to Colby's equation because of the complete control achieved.…”
Section: Ivyleaf Morningglorymentioning
confidence: 74%
“…A similar situation occurs with common ragweed, ivyleaf morningglory, and sicklepod, which are also pervasive and hard-to-control weeds in the southeastern United States (Jones et al 2022;Van Wychen 2017;Webster and Nichols 2012). Previous research has shown that dicamba and glufosinate are effective on these species; however, mixtures and sequential applications of these herbicides have not been evaluated (Everman et al 2007;Kalina et al 2021;Leon et al 2016;Schrage 2018). The objectives of this study were to determine (1) if the order of dicamba and glufosinate in a sequential application influence control on certain weed species and sizes and (2) if dicamba þ glufosinate mixtures demonstrate an antagonistic interaction on certain weed species and sizes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Stem density for the glyphosate-applied-alone treatments, whether made during the day or night, were not different from the nontreated check (P values = 0.331 and 0.332, respectively). Numerous studies have reported that herbicide applications made in the morning or mid-day hours perform better than applications made at night or during early-morning hours (Copeland et al 2019;Johnston et al 2018;Kalina et al 2022;Martinson et al 2002;Miller et al 2003;Stopps et al 2017). However, many other factors can affect herbicide efficacy, such as herbicide site of action, plant species, and environmental conditions.…”
Section: Reardanmentioning
confidence: 99%